Peningkatan Pengetahuan Tentang Garis Bilangan Melalui Permainan Loncat Garis (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
There are some students who are still low in understanding students' mathematical concepts in the subject matter of integer addition operations in mathematics. The purpose of this study was to analyze how students' understanding of concepts in mathematics about the arithmetic operation of addition of integers using the media of a number line. The results of the research show that the use of number line media in learning the addition of integers significantly improves understanding of the concept student math. This media assists students in visualizing the process of adding integers and understanding positive-negative concepts and their relationship to the number line. In addition, the use of number line media also provides benefits in improving students' mathematical computing skills, such as understanding addition operations, pattern recognition, and determining sum results.